Scaling up qualitative research to harness the capacity of lay people in invasive plant management. Issue 6 (27th July 2022) - Gill, Nicholas; Chisholm, Laurie; Atchison, Jennifer; Graham, Sonia; Hawkes, Gina; Head, Lesley; McKiernan, Shaun
Abstract: Successful management of invasive plants (IPs) requires the active participation of diverse communities across land tenures. This can be challenging because communities do not always share the views of scientists and managers. They may directly disagree, have alternative views, or be unwilling to manage IPs. Reviews of IP social science identify opportunities to better understand the role of cultural processes and everyday practices to address these challenges. To scale up and leverage the insights of existing qualitative social science IP research, we used meta‐ethnography to unlock accounts and interpretations of lay perspectives. Meta‐ethnography is a form of qualitative research synthesis increasingly used beyond its origins in health and education to produce interpretive syntheses of an area of research. In the 7 phases of meta‐ethnography, we systematically identified and synthesized 19 qualitative articles pertinent to lay experience and knowledge of IPs in diverse settings. Action and meaning regarding IPs were influenced by 6 meta‐themes in personal and social life: dissonance, priorities, difference, agency, responsibility, and future orientations. Through descriptions and examples of each meta‐theme, we demonstrated how the meta‐themes are higher level structuring concepts across the qualitative research that we analyzed and we retained grounding in the in‐depth qualitative research. We characterized the meta‐themes as leverage points and tensions by which we reframed lay people in terms of capacity for reflective IP management rather than as obstacles. The meta‐ethnography synthesis shows how leverage points and tensions emerge from everyday life and can frame alternative and meaningful starting points for both research and public engagement and deliberation regarding IP management. These insights are not a panacea, but open up new space for reflective and mutual consideration of how to effectively navigate often complex IP problems and address conservation and social and livelihood issues in dynamic social and physical environments. Abstract : Aprovechamiento de la Capacidad de la Gente Común en el Manejo de Plantas Invasoras Resumen: El manejo exitoso de las plantas invasoras requiere de la participación de las diferentes comunidades participantes en la tenencia de tierras. Esto puede ser un reto porque las comunidades no siempre comparten las opiniones de los científicos y los gestores. Puede que las comunidades estén en desacuerdo directo con estas opiniones, tengan opiniones alternativas o no estén dispuestas a manejar las plantas invasoras. Las revisiones a las ciencias sociales de las plantas invasoras identifican oportunidades para entender de mejor manera el papel de los procesos culturales y las prácticas diarias para abordar estos retos. Usamos la meta‐etnografía para revelar explicaciones e interpretaciones de las perspectivas comunes para aumentar y potenciar el conocimiento cualitativo de las investigaciones en ciencias sociales de las plantas invasoras. La meta‐etnografía es una forma de síntesis de la investigación cualitativa que se usa cada vez más fuera de sus orígenes en la salud y educación para producir síntesis interpretativas de un área de investigación. En las siete fases de la meta‐etnografía identificamos y sintetizamos sistemáticamente 19 artículos cualitativos correspondientes a la experiencia y el conocimiento no profesional de las plantas invasoras en diferentes escenarios. Las acciones y significados con respecto a las plantas invasoras estuvieron influenciadas por seis meta‐temas en la vida personal y social: disonancia, prioridades, diferencia, agencia, responsabilidad y orientaciones a futuro. Por medio de descripciones y ejemplos de cada meta‐tema, demostramos cómo estos son conceptos estructuradores de nivel más alto a lo largo de la investigación cualitativa que analizamos y mantuvimos basados en la investigación cualitativa a profundidad. Caracterizamos los meta‐temas como puntos de potenciación y tensiones por la cual replanteamos a la gente común en términos de capacidad de reflexión en el manejo de plantas invasoras en lugar de considerarlas obstáculos. La síntesis de la meta‐etnografía muestra cómo los puntos de potenciación y las tensiones emergen de la vida cotidiana y pueden plantear puntos de partida alternativos y significativos para la investigación, la participación pública y la deliberación en el manejo de plantas invasoras. Esta información no es la panacea, pero puede abrir un espacio nuevo para la consideración mutua y reflexiva de cómo navegar efectivamente los problemas complejos de las plantas invasoras y cómo abordar los temas de conservación social y de sustento en los ambientes dinámicos sociales y físicos. 【摘要】: 入侵植物的成功管理需要不同土地制度的社区的积极参与。这可能是一个挑战, 因为社区居民并不总是认同科学家和管理者的观点。他们可能会直接反对、持不同观点, 或不愿意管理入侵植物。对入侵植物的社会科学综述有助于更好地了解文化过程和日常实践的作用, 以应对这些挑战。我们使用元民族志来展示非专业人士观点的描述和理解。元民族志是一种定性研究综述的形式, 起源于卫生和教育领域, 已被越来越多地被用于对一个研究领域进行诠释性的综述。在元民族志的 7 个阶段中, 我们系统地确定并概括了 19 篇与不同环境中非专业人士对入侵植物的经验和知识有关的定性文章。我们发现, 关于入侵植物的行动和意义受到个人和社会生活中 6 个元主题的影响: 不协调性、优先性、差异、机构、责任和未来方向。通过对每个元主题的描述和举例, 我们展示了元主题如何在我们分析的定性研究中形成更高层次的结构性概念, 并且我们在深入的定性研究中保留了基础。我们将元主题描述为杠杆点和张力, 在此基础上, 我们将非专业人士重新定义为思考入侵植物管理的能力, 而非障碍。元民族志的整合显示了杠杆点和张力如何出现在日常生活中, 且可以为有关入侵植物管理的研究和公众参与及讨论提供有意义的替代性起点。这些见解不能解决所有问题, 但可以为反思和交互性考虑如何有效管理复杂的入侵植物问题, 以及在动态的社会和物理环境中解决保护和社会及生计问题开辟了新的空间。【翻译: 胡怡思; 审校: 聂永刚】